Effects of different jump-landing directions on sagittal plane kinematics, kinetics and energy dissipation at lower extremity joints - Lee, Y. -M.; Lee, H. -J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the effects of different jump-landing directions on sagittal plane kinematics, kinetics, and energy dissipation. Subjects were required to perform a double-leg jump at three directions to a height equivalent to 50% of their maximum vertical jump height and land with single-leg and maintain balance for three seconds. Our findings indicated that landing strategy changed across different jump-landing directions in a way that maintained the same level of shock attenuation via altering body position and using the knee and ankle joints as primary dissipaters. We suggested that the knee joint showed major contributions to energy dissipation at forward and diagonal directions, and increased the use of ankle joint to dissipate energy while landing at lateral direction.